Pengaruh E-Service Quality, Kualitas Layanan Logistik, Kesadaran Merek, Kepercayaan, dan Kepuasan terhadap Loyalitas Pelanggan pada Aplikasi Shopee (Studi Pada Mahasiswa Universitas Muhammadiyah Purwokerto) - Fadila Saputri; Dian Widyaningtyas; Akhmad Darmawan; M. Agung Miftahuddin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
With a focus on respondents from Muhammadiyah University of Purwokerto, this research seeks to examine the relationship between customer loyalty on the Shopee app and factors such as E-Service Quality, Logistics Service Quality, Brand Awareness, Trust, and Satisfaction. The study employs a quantitative approach using a survey method, distributing questionnaires to 100 active students of Universitas Muhammadiyah Purwokerto who are active Shopee users. The data were analyzed using multiple linear regression with SPSS version 26. The results indicate that all five independent variables have a positive and significant effect on customer loyalty, with trust and customer satisfaction emerging as the most dominant factors. Trust shows the strongest influence on customer loyalty (β = 0.432; p < 0.05), followed by satisfaction (β = 0.335). Simultaneously, the five variables explain 74.8% of the variance in customer loyalty, emphasizing the crucial role of trust and satisfaction in retaining Shopee users in the student segment. These findings support the view that in-house logistics services, such as Shopee Express, can be managed more effectively in terms of quality to enhance trust, satisfaction, and loyalty. The study may help Shopee remain competitive by highlighting the importance of improving service quality and digital technologies. This research also contributes theoretically to the existing literature on consumer loyalty in Indonesia’s online marketplace context.